2020
DOI: 10.1155/2020/7268519
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Multidrug-Resistant Bacteria in Lower Respiratory Tract Infections: A Systematic Review and Meta-Analysis

Abstract: Background. Multidrug-resistant (MDR) bacteria are the main cause of lower respiratory tract infections (LRTIs) with high mortality. The purpose of this study is to identify the risk factors associated with MDR by performing a systematic review and meta-analysis. Methods. PubMed, EMBASE (via Ovid), and Cochrane Library were systematically searched for studies on the risk factors for MDR bacteria in LRTIs as of November 30, 2019. Literature screening, data abstraction, and quality assessment of the eligible stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Even though S. pneumoniae is the most prevalent cause of CAP in all age groups around the world, gram-negative bacteria (GNB) such as K. pneumoniae, Acinetobacter baumannii, P. aeruginosa, and E. coli are commonly related to HAP [ 3 , 16 , 17 ]. Antibiotic resistance is increasingly being recognized as a major worldwide health concern resulting from antibiotic overuse and improper administration [ 18 ]. Nowadays, pneumonia caused by multidrug-resistant gram-negative bacteria (MDR-GNB) is growing more common and has a detrimental impact on patient outcomes, indicating a shift in infection trends to GNB and their rapid dissemination, particularly in the hospital settings [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though S. pneumoniae is the most prevalent cause of CAP in all age groups around the world, gram-negative bacteria (GNB) such as K. pneumoniae, Acinetobacter baumannii, P. aeruginosa, and E. coli are commonly related to HAP [ 3 , 16 , 17 ]. Antibiotic resistance is increasingly being recognized as a major worldwide health concern resulting from antibiotic overuse and improper administration [ 18 ]. Nowadays, pneumonia caused by multidrug-resistant gram-negative bacteria (MDR-GNB) is growing more common and has a detrimental impact on patient outcomes, indicating a shift in infection trends to GNB and their rapid dissemination, particularly in the hospital settings [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the associated morbidity and high finical burden within hospital settings, the microbiological diagnosis of HAP/VAP remains challenging. Of concern, the difficulty in obtaining a reliable LRT specimen by non-invasive techniques [6], the wide range of microbial profiles (bacteria, virus, or, rarely, fungi) [7], the escalating threats of multidrugresistant (MDR) bacteria, and the long turnaround time of about 2-3 days to obtain culture results further complicated the ability to diagnose by conventional means [8,9]. However, microbiological methods are necessary in guiding empiric antibiotic regimens and prescribing appropriate treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…We had a higher rate of MDROs in our patient population compared to other studies of tracheostomy and ventilation-dependent children 15 . 76% of our participants had at least one respiratory tract culture with a MDRO.…”
Section: Discussionmentioning
confidence: 63%
“…We found that frequent hospitalizations and antibiotic usage increased the risk of MDRO in the respiratory tract of technology-dependent children. It has been shown that hospitalizations and prior antibiotic usage were independent risk factors for lower respiratory tract MDROs in adults, but has not been well described in children 15 . We also found that both intermittent antibiotic usage and chronic antibiotics increased risk of MDRO.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation